Metal promiscuity and metal-dependent substrate preferences of Trypanosoma brucei methionine aminopeptidase 1 - Marschner, Aline; Klein, Christian D. (Biochimie, 2015)
Methionine aminopeptidases play a major role in posttranslational protein processing and are therefore promising targets for the discovery of novel therapeutical agents. We here describe the heterologous expression, purification, and characterization of recombinant Trypanosoma brucei methionine aminopeptidase, type 1 (TbMetAP1). We investigated the dependency of TbMetAP1 activity on pH and metal cofactor (type and concentration) using in particular the substrates Met-Gly-Met-Met and Met-AMC along with related compounds, and determined kinetic values (Km, vmax, kcat). The optimal pH for TbMetAP1 activity is between 7.0 and 8.0. Surprisingly, the two substrates have different cofactor requirements: Both substrates are processed by the cobalt-activated TbMetAP1, but only the Met-Gly-Met-Met substrate is processed with nearly identical catalytical properties by the zinc-activated enzyme. Depending on the substrate, various other metal ions (iron(II), manganese, nickel) were also accepted as cofactors. Two aspects of this work are relevant for the biochemistry of MetAPs and further drug discovery efforts: 1. Zinc, and not cobalt ions are probably the physiological cofactor of TbMetAP1 and possibly other MetAPs. 2. In MetAP assays for compound screening, the combination of the Met-AMC substrate with cobalt, manganese or iron ions may not represent the physiological reality, thereby leading to results that can not be extrapolated towards a phenotypic effect.